Intorno alla friulanita (e alle essenze etniche) - Gri, Gian Paolo (Traditiones (Ljubljana), 1999)
How should one understand the Friulian identity? The paper tries to provide answer by means of "open" and dynamic categories employed by cultural anthropology in relation to multiethnicity, multilingualism, acculturation, contacts with and belonging to different cultures
Keywords: Friuli–Venezia Giulia; Furlanija; Italija; Italy; kulturna zgodovina